PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK (LKPD) DENGAN PENDEKATAN SCIENCE, ENVIRONMENT, TECHNOLOGY, AND SOCIETY (SETS) PADA MATA PELAJARAN KIMIA SMA POKOK BAHASAN HIDROKARBON - Rica Rahmawati; Johni Azmi; Betty Holiwarni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research is a Research and Development (R & D). The development process has been done with reference to 4-D model with steps of Defenition, Design, Development, and Disseminate. Research was conducted in FKIP UR. This research aims to obtain a student worksheet with Science, Environment, Technology and Society (SETS) approach on chemistry subject Senior High School of hydrocarbon . The research and development with 4-D model was conducted only until Development step, because the purpose of this research was limited to develop and produce a valid student worksheet to be implemented based on validator assessment. Feasibility of student worksheet was evaluated from feasibility of content, language, presentation, graphical and scientific approach aspects. Student worksheet validation result obtained an average value as 91,49% which showed that student worksheet which developed was valid. Means, student worksheet with Science, Environment, Technology and Society (SETS) approach on chemistry subject Senior High School of hydrocarbon that was developed, suitable to be used in learning process.Keyword : SETS Approach, Worksheet Students, and Hydrocarbon